2020
DOI: 10.20944/preprints202008.0145.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mapping Research on Customer Centricity and Sustainable Organizations

Abstract: Firms are increasingly organized around the client. At the same time, there is customer pressure on green and sustainable organizations. The purpose of this paper is to map the current state of the research in the domain of customer-centric organizations from a sustainable perspective. We conducted a bibliometric analysis from published documents between 1990 and 2020. Key findings indicate that research on customer centricity and sustainability has increased in recent years and that the topic is structured in… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 54 publications
(75 reference statements)
0
8
0
Order By: Relevance
“…It is possible to present the results of the two phases of the study: the first phasethe co-occurrence analysis of selected papersconsists in identifying the presence of studies at the theoretical level that combine CES with CEM. This phase allowed us to identify the main theoretical topics that appeared as clusters through VOSviewer software, namely "consumer behavior", "decision making", "business development" and "co-creation", which confirm and advance the exploratory study of Pardo-Jaramillo et al (2020). The qualitative MD 61,13 analysis in the case study within the food delivery industry (phase 2 of the study) has been used to validate the theoretical issues identified in the first phase.…”
Section: P4mentioning
confidence: 98%
See 4 more Smart Citations
“…It is possible to present the results of the two phases of the study: the first phasethe co-occurrence analysis of selected papersconsists in identifying the presence of studies at the theoretical level that combine CES with CEM. This phase allowed us to identify the main theoretical topics that appeared as clusters through VOSviewer software, namely "consumer behavior", "decision making", "business development" and "co-creation", which confirm and advance the exploratory study of Pardo-Jaramillo et al (2020). The qualitative MD 61,13 analysis in the case study within the food delivery industry (phase 2 of the study) has been used to validate the theoretical issues identified in the first phase.…”
Section: P4mentioning
confidence: 98%
“…In a nutshell, from the bibliometric analysis and the empirical case study emerges the potential for a new model that incorporates the attributes and characteristics of CEM and CES by integrating them to take advantage of the benefits of both (Pardo-Jaramillo et al, 2020). The new model, shown in Figure 5, summarizes and integrates the findings of the twophase analysis.…”
Section: The Development Of An Integrated Framework and Propositionsmentioning
confidence: 99%
See 3 more Smart Citations